PENGARUH PENAMBAHAN SARI BUAH MANGGA (MANGIFERA INDICA) TERHADAP PEMBUATAN SIRUP BUAH MANGROVE PEDADA (SONNERATIA CASEOLARIS) - Novitasari, Maya; Nurfadilah, Nurfadilah (Sekolah Tinggi Perikanan dan Kelautan (STPL) Palu, 2020)
Syrup is a kind of drink in the form of a thick solution with diverse flavors that are not directly drunk but must be diluted first. Dilution is needed because the sugar content in syrup is high, which is between 55% - 65%. The making of syrup can be added with coloring and citric acid to add color and flavor. The purpose of this study was to determine the panelists' acceptance of the manufacture of syrup using raw materials of mangrove fruit. While the benefits of this study researchers are expected to improve their knowledge and skills in processing Mangrove Pedada Fruit (Sonneratia caseolaris) so that they are able to develop the science and technology of processing Mangrove Pedada Fruit (Sonneratia caseolaris) in Central Sulawesi. This research will be carried out in December 2019, at the Applied Marine Products Processing Technology Laboratory, Palu Polytechnic. This study uses RAK (Randomized Block Design) with 3X organploptic test replications, the treatment applied is the addition of mango juice in the production of mangrove fruit syrup (Sonneratia caseolaris) consisting of 5 treatments, each Mangrove juice 0 ml, 150 ml, 175 ml, 200 ml and 250 ml. What was observed was organoleptic which included thickness, color, taste and aroma. Pedada Mangrove Syrup (Sonneratia caseolaris) with the addition of Mango juice (Mangifera indica) is best obtained in the treatment of p1 with an orange color, aroma, taste and thickness that resembles juice in general. Further research needs to be done about the shelf life of Pedada Mangrove Fruit Syrup (Sonneratia caseolaris) with the addition of different Mango Juice (Mangifera indica).